Drug therapy for the management of cancer-related fatigue. - Minton, O; Richardson, A; Sharpe, M; Hotopf, M; Stone, P (2010)
BACKGROUND: This is an updated version of the original Cochrane review published in issue 1 2008 (Minton 2008). Cancer-related fatigue (CRF) is common, under-recognised and difficult to treat. There have been studies looking at drug interventions to improve CRF but results have been conflicting depending on the population studied and outcome measures used. No previous reviews of this topic have been exhaustive or have synthesised all available data. OBJECTIVES: To assess the efficacy of drugs for the management of CRF. SEARCH STRATEGY: We searched the Cochrane Central Register of Controlled Trials (from Issue 2 2007) MEDLINE and EMBASE from January 2007 to October 2009 and a selection of cancer journals. We searched references of identified articles and contacted authors to obtain unreported data. SELECTION CRITERIA: Studies were included in the review if they 1) assessed drug therapy for the management of CRF compared to placebo, usual care or a non-pharmacological intervention in 2) randomised controlled trials (RCT) of 3) adult patients with a clinical diagnosis of cancer. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trial quality and extracted data. Meta-analyses were performed on different drug classes using continuous variable data. MAIN RESULTS: Fifty studies met the inclusion criteria. Six additional studies were identified since the original review. Only 31 of these studies involving 7104 participants were judged to have used a sufficiently robust measure of fatigue and thus were deemed suitable for detailed analysis. The drugs were still analysed by class (psychostimulants; haemopoietic growth factors; antidepressants and progestational steroids). Methylphenidate showed a small but significant improvement in fatigue over placebo (Z = 2.83; P = 0.005). Since the publication of the original review increased safety concerns have been raised regarding erythropoietin and this cannot now be recommended in practice.There was a very high degree of statistical and clinical heterogeneity in the trials and the reasons for this are discussed. AUTHORS' CONCLUSIONS: There is increasing evidence that psychostimulant trials provide evidence for improvement in CRF at a clinically meaningful level. There is still a requirement for a large scale RCT of methylphenidate to confirm the preliminary results from this review. There is new safety data which indicates that the haemopoietic growth factors are associated with increased adverse outcomes. These drugs can no longer be recommended in the treatment of CRF. Readers of the first review should re-read the document in full.